Combining the platinum(ii) drug candidate kiteplatin with 1, 10-phenanthroline analogues. Issue 7 (1st December 2017) - Pages, Benjamin J.; Sakoff, Jennette; Gilbert, Jayne; Zhang, Yingjie; Kelly, Sharon M.; Hoeschele, James D.; Aldrich-Wright, Janice R.
Abstract : Drug candidate kiteplatin has been combined with analogues of 1, 10-phenanthroline, and the DNA affinity and cytotoxicity have been assessed. Abstract : Platinum complexes of the type [Pt(PL )(AL )] 2+ where PL is a derivative of 1, 10-phenanthroline and AL is cis -1, 4-diaminocyclohexane (1, 4-dach), have been synthesised and characterised by ultraviolet spectroscopy, elemental microanalysis, nuclear magnetic resonance and X-ray crystallography. The calf-thymus DNA binding affinity of these complexes was determined by isothermal titration calorimetry, revealing higher DNA affinity than their 1 S, 2 S -diaminocyclohexane analogues. In vitro cytotoxicity was assessed in eleven human cell lines, revealing unexpectedly low activity for the 1, 4-dach complexes.